Plasma polymer barrier layers to control the release kinetics from dissolvable microneedle patches. Issue 12 (28th July 2022) - González García, Laura E.; MacGregor, Melanie; Cavallaro, Alex; Koynov, Kaloian; Vasilev, Krasimir
Abstract: Dissolving microneedles are a noninvasive transdermal drug delivery platform that offers painless needle‐free patient treatment. Current strategies to control the kinetics of drug release from the polymeric microneedle patches consist of adjusting the bulk polymer formulations and/or encapsulating the cargo in controlled delivery vehicles. Instead, in this study, the drug release rates were altered by modifying the surface properties of the microneedles using plasma polymer coatings with tailored properties. The main advantage of this one‐step, solvent‐free, and scalable method is that it can be applied to any type of microneedles regardless of their drug cargo or bulk material. Octadiene plasma polymer films were found to suppress the burst release effect of otherwise rapidly dissolving microneedles and to reduce the dissolution rate by a factor of four compared to uncoated control patches. The approach presented in this study offers an alternative, highly tunable, and customizable strategy for controlling drug release rate from microneedle patches. Abstract : Hydrophobic plasma polymer coatings reduce the drug release rate from dissolving microneedle patches. In this report, we provide for the first time a proof of concept demonstration that plasma polymers deposited onto dissolving microneedle patches can be used to alter the drug release kinetics. Octadiene coatings suppressed the burst release from cellulose microneedles, reducing their dissolution rate by a factor of four.